Forest restoration in a time of fire: perspectives from tall, wet eucalypt forests subject to stand-replacing wildfires - Lindenmayer, David B.; Bowd, Elle J.; Gibbons, Philip (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2023)
Wildfires have the potential to add considerably to the already significant challenge of achieving effective forest restoration in the UN Decade on Ecosystem Restoration. While fire can sometimes promote forest restoration (e.g. by creating otherwise rare, early successional habitats), it can thwart it in others (e.g. by depleting key patch types and stand structures). Here we outline key considerations in facilitating restoration of some tall wet temperate forest ecosystems and some boreal forest ecosystems where the typical fire regime is rare high-severity stand-replacing fire. Some of these ecosystems are experiencing altered fire regimes such as increased fire extent, severity and/or frequency. Achieving good restoration outcomes in such ecosystems demands understanding fire regimes and their impacts on vegetation and other elements of biodiversity and then selecting ecosystem-appropriate management interventions. Potential actions range from doing nothing (as the ecosystem already maintains full post-fire regenerative capacity) to interventions prior to a conflagration like prescribed burning to limit the risks of high-severity fire, excluding activities that impair post-fire recovery (e.g. post-fire logging), and artificial seeding where natural regeneration fails. The most ecologically effective actions will be ecosystem-specific and context-specific and informed by knowledge of the ecosystem in question (such as plant life-history attributes) and inter-relationships with attributes like vegetation condition at the time it is burnt (e.g. young versus old forest). This article is part of the theme issue ‘Understanding forest landscape restoration: reinforcing scientific foundations for the UN Decade on Ecosystem Restoration’.